Early rising asexual parasitaemia in Nigerian children following a first dose of artemisinin-based combination treatments of falciparum malaria. Issue 1 (December 2017) - Sowunmi, Akintunde; Akano, Kazeem; Ayede, Adejumoke; Adewoye, Elsie; Ntadom, Godwin; Fatunmbi, Bayo; Gbotosho, Grace; Folarin, Onikepe; Happi, Christian
Abstract Background Early rising asexual parasitaemia (ERAP), initially defined as 'an increase in the parasite count over the baseline pre-treatment level during the first 24 h of treatment' of falciparum malaria with artemisinin derivatives is well documented, but there is no characterization of its risk factors, kinetics, molecular features or relationship to late-appearing anaemia (LAA) in acute falciparum malaria in African children following oral artemisinin-based combination therapies (ACTs). Methods ERAP was defined as ≥5% increase in pre-treatment parasitaemia within 8 h of initiating treatment. Parasitaemia was quantified pre-treatment and 1–2 hourly for 8 h, and less frequently thereafter for 6 weeks following randomized treatment of acutely malarious children with artesunate-amodiaquine, artemether-lumefantrine or dihydroartemisinin-piperaquine. Risk factors were determined by stepwise multiple logistic regression model. Kinetics of release into and of elimination of asexual parasites and DNA clones from peripheral blood were evaluated by method of residuals and non-compartment model, respectively. Parasite population changes were evaluated morphologically and by molecular genotyping. Results ERAP occurred in 205 of 416 children. A parasitaemia <100, 000/μL and parasitaemia 1 day post-treatment initiation were independent predictors of ERAP. In children with ERAP: mean and peak time of increase in parasitaemia were 105.6% (95% CI 81–130.1) and 2.5 h (95% CI 2.2–2.7), respectively. Mean lag time, half-time and rate constant of release were 0.2 h (95% CI 0.2–0.3), 1 h (95% CI 0.9–1.1), and 0.9 h−1 (95% CI 0.8–1), respectively. Schizonts and young gametocytes were seen only in peripheral blood of few children with ERAP. In age-, gender-, baseline parasitaemia- and treatment-matched children with and without ERAP, parasite DNA clearance time and area under curve of number of DNA clonesversus time were significantly higher in children with ERAP indicating peripheral retention of released parasites followed by elimination. DNA clone elimination was monoexponential. Conclusion ERAP is common, occurs rapidly as first order process and may be due to mobilization of parasites from deep tissue following a first dose of ACTs of acute childhood falciparum malaria. Trials registration Pan African Clinical Trial RegistryPACTR201508001188143, 3 July 2015; PACTR201510001189370, 3 July 2015; PACTR201508001191898, 7 July 2015 and PACTR201508001193368, 8 July 2015.